Editor’s Role in Event Video Loop Visual Identity - Sutan Muhammad Aqil; Dynia Fitri (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Video loops are visual media used in events to build atmosphere and strengthen audience identity. The Bundafest Haibunda event utilizes video loops with a specific visual style aimed at mothers and families.This study aims to analyze the role of editors in shaping the visual identity of the Bundafest Haibunda eventvideo loops. The research uses a qualitative approach with participant observation methods, in which theauthor is directly involved as an editor in the production process. Data is obtained through observation ofthe editing process, visual documentation, and work experience reflections, then analyzed using RolandBarthes' semiotic approach which includes denotation, connotation, and myth. The results show that the editor's decisions in color selection, editing rhythm, and visual consistency play an important role inconstructing the meaning of warmth, cheerfulness, and emotional closeness. At the mythical level, the video loop represents the image of modern mothers as active, positive, and adaptive figures in the digitalspace. This study confirms that editors do not only play a technical role but also act as strategic actors inthe production of event-based media visual identities.